Cost of Community-Based HIV Testing Activities to Reach Saturation in Botswana. - Lasry, Arielle; Bachanas, Pamela; Suraratdecha, Chutima; Alwano, Mary Grace; Behel, Stephanie; Pals, Sherri; Block, Lisa; Moore, Janet (AIDS & Behavior, 2019)
In Botswana, 85% of persons living with HIV are aware of their status. We performed an economic analysis of HIV testing activities implemented during intensive campaigns, in 11 communities, between April 2015 and March 2016, through the Botswana Combination Prevention Project. The total cost was $1,098,312, or $99,847 per community, with 60% attributable to home-based testing and 40% attributable to mobile testing. The cost per person tested was $44, and $671 per person testing positive (2017 USD). Labor costs comprised 64% of total costs. In areas of high HIV prevalence and treatment coverage, the cost of untargeted home-based testing may be inflated by the efforts required to assess the testing eligibility of clients who are HIV-positive and on ART. Home-based and mobile testing delivered though an intensive community-based campaign allowed the identification of HIV positive persons, who may not access health facilities, at a cost comparable to other studies.